An evaluation of the environmental benefit and energy footprint of China's stricter wastewater standards: Can benefit be increased?. (10th May 2019) - Smith, Kate; Guo, Shengjie; Zhu, Qinhan; Dong, Xin; Liu, Shuming
Abstract: In 2015, almost 25% of China's lakes were polluted to the point of being unfit for any purpose. In the same year, China introduced plans to upgrade hundreds of existing and planned wastewater treatment plants to China's highest standard for wastewater discharge. The goal of this paper is two-fold. Firstly, it aims to help policy makers in China understand the impact of China's new wastewater standard on energy use. Secondly, it aims to provide policy makers with suggestions to increase the environmental benefit gained from reducing wastewater contaminant discharge. The most recent data from around 5000 wastewater treatment plants in China are used to estimate the extra electricity required to upgrade a plant from China's commonly used Class 1B municipal wastewater discharge standard to the highest discharge standard, Class 1A. Results show that implementing Class 1A instead of Class 1B tends to use 2%–36% more electricity. This result was used to estimate the overall increase in electricity used over five years by the Chinese wastewater sector due to the introduction of the new policy, an increase that was estimated to be 3–63% of annual electricity used for wastewater treatment. The environmental benefit and electricity cost of three scenarios aimed at reducing wastewater contaminant discharge were compared. Results showed that the benefit-to-cost ratio of implementing stricter standards is greatly improved (by over seven times) when wastewater is not discharged into the environment but instead reused to replace freshwater for purposes that can be met with Class 1A standard. This result has implications for policy makers seeking to increase energy use efficiency, minimise water wastage and reduce environmental pollution within cities. Graphical abstract: Image 1 Highlights: China's new wastewater standards are highly likely to increase electricity use. The highest standard tends to use 2–36% more electricity than the second highest. Results are based on a decade of data for thousands of treatment plants in China. Benefit of strict treatment can be increased over 7 times by wastewater reuse. Collecting and treating untreated wastewater has greatest benefit-to-cost ratio.